ANALYSIS OF CONSUMER PREFERENCES FOR BROILER CHICKEN MEAT IN THE TRADITIONAL MARKET OF MAGELANG CITY - Afiifah Cahya Fadila; Wahyu Dyah Prastiwi; Mukson Mukson (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2025)
The increasing consumption of broiler chicken meat in society indicates a significant shift in consumption patterns. This highlights the importance of understanding the factors influencing consumer preferences for this product. The study aimed to analyze consumer preferences by identifying the most critical attributes of broiler chicken meat and the preferred attribute combinations in traditional markets of Magelang City. This research was conducted from December 2023 to January 2024 in conventional markets in Magelang City. The research location was chosen because Magelang City has five traditional markets, four of which sell broiler chicken meat, and the increasing broiler chicken production in the city in 2023. The study employed a survey method, with a non-probability sampling approach using accidental sampling, as determined through Lemeshow’s formula. This formula was used to determine a representative sample size based on the desired confidence level and margin of error. The study involved 400 respondents whose characteristics were analyzed based on gender, age, occupation, income, number of family members, and food expenditure. The collected data included both primary and secondary data. Primary data were gathered through interviews and offline questionnaires, while secondary data were obtained from institutions such as BPS and relevant journals. The data were analyzed using descriptive analysis and Conjoint analysis. The results of the study showed that (1) consumers prefer broiler chicken meat priced at Rp32,000 – Rp35,000, with white skin color, meat weighing >1.8 kg, fresh condition, and carcasses cut into eight pieces; (2) the relative order of importance most considered by consumers in buying broiler chicken meat is color, form, price, size, and carcass cut size.